Unbounded love a good news theology for the 21st century - Pinnock, Clark H. 1937-; Brow, Robert C. (Downers Grove, IL IVP, 1994)
Includes bibliographical references.
Keywords: Theology, doctrinal; God -- worship and love; Love -- religious aspects -- Christianity; Evangelicalism